2017
DOI: 10.1007/s10072-017-2999-1
|View full text |Cite
|
Sign up to set email alerts
|

Definitive childlessness in women with multiple sclerosis: a multicenter study

Abstract: The frequency of definitive childlessness in women with multiple sclerosis (MS) may be higher than in the general population. MS may also affect decisions on the delivery procedure and on breast-feeding issues. Aim of the study was to assess the frequency of childlessness and its possible causes, the proportion of cesarean deliveries (CD), and the frequency of breast-feeding in patients and controls who have reached the end of their reproductive period. Female MS patients (>43 years) and controls (>45 years) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 28 publications
2
32
0
1
Order By: Relevance
“…In the present study, 88.2% of the mothers have been housewives and this indicates a specific social inactivity in this group, which may be due to the reduction of childbearing. Studies also showed that women with a higher socioeconomic level tended to delay pregnancy (19). Considering that about 45% of the subjects had university education and most of the subjects of the study enjoyed a moderate economic level, it seems the results of our study also indicate that with increasing social and economic level, the tendency to delay and decrease in childbearing increases.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the present study, 88.2% of the mothers have been housewives and this indicates a specific social inactivity in this group, which may be due to the reduction of childbearing. Studies also showed that women with a higher socioeconomic level tended to delay pregnancy (19). Considering that about 45% of the subjects had university education and most of the subjects of the study enjoyed a moderate economic level, it seems the results of our study also indicate that with increasing social and economic level, the tendency to delay and decrease in childbearing increases.…”
Section: Discussionsupporting
confidence: 61%
“…The mean number of pregnancies in women with MS was 1.61 in the studied population. Ferraro's study in 2017 indicated that MS disease was associated with an increase in the number of unmarried women compared to the general population (22% versus 13%) (19). A study in France also found that 30% of women with MS had no children, although in this study women were still at reproductive ages (20).…”
Section: Discussionmentioning
confidence: 52%
“…Pregnancy is still a major concern for the majority of woman diagnosed with MS. Recently, an Italian study investigated childlessness in female MS patients (N ¼ 303) and agematched controls (N ¼ 500) once they reached the end of their reproductive period (>43 years of age) 29 . Sixty-seven MS women (22%) were childless compared with 66 controls (13%).…”
Section: Preconception Period In Women With Msmentioning
confidence: 99%
“…suggests that anti‐Müllerian hormone, the marker for ovarian reserve, is significantly reduced in women with MS . However, MS is associated with a higher frequency of voluntary childlessness (22% versus 13% in women without MS) and many more women with MS will choose to terminate their pregnancy than those without the disease (20% versus 12%) . Reasons for voluntary childlessness and termination most often cited in the published literature are disability or fear of disability, fear of transmitting MS to offspring, fear of discontinuing medications and discouragement from physicians.…”
Section: Effects Of Ms On Pregnancymentioning
confidence: 99%